A study of cash waqf contribution between millennials of Malaysia and Indonesia - Anwar Allah Pitchay; Raditya Sukmana; Ririn Tri Ratnasari; Mohamad Isa Abd Jalil (Emerald, 2023)
Purpose – This study aims to examine the determinants of motivation that influences Malaysian and Indonesian millennials to contribute cash waqf. Design/methodology/approach – The present study used self-determination theory and 423 respondents, of which 205 respondents are from Malaysia and 218 from Indonesia. The study developed a self-administrative questionnaire, and it is distributed through an online survey method, and the data are analysed using SmartPLS partial least squares analysis. Findings – The results show that perceived donor effectiveness and moral obligation factors influence both Malaysians and Indonesian millennials to make cash waqf contributions. Meanwhile, the face concern factor did not significantly affect millennials in Malaysia and Indonesia to contribute cash waqf. Furthermore, the sense of self-worth factor appears to significantly influence only Indonesian millennials but not Malaysian millennials. Research limitations/implications – The research findings have significant theoretical and practical ramifications. Firstly, while face concern has a positive effect on millennials’ willingness to contribute cash to waqf, it is not statistically significant in Muslim populations. This implies that to persuade millennials to make cash waqf contributions, the face concern argument should be avoided. Originality/value – The comparative study between Malaysia and Indonesia adds new value to this study. These two Muslim majority countries have similar attributes in terms of religion, demography and race background. Furthermore, the focus of this study, which targets units of analysis from millennials, has received very little attention in the literature related to cash waqf.